2 Chronic dietary exposure to multiple pesticides during pregnancy and risk of hypospadias: the french elfe birth cohort. (18th March 2018) - Souleymane-Cognez, Noriane; Warembourg, Charline; Zaros, Cécile; Garlantezec, Ronan; Charles, Marie-Aline; Béranger, Rémi; Chevrier, Cécile
Abstract : Background/aim: Prenatal occupational exposure to pesticides has been associated to congenital malformations, but little is known about the effect of dietary exposure in the general population. Exposure to various pesticides through dietary intake has been recently assessed in French pregnant women. We aimed to study its association with the risk of hypospadias. Methods: Among 7035 boys enrolled in 2011 the French national birth cohort Elfe, 46 have been diagnosed with hypospadias. Maternal daily intakes were estimated for 317 pesticides, based on a validated self-administered food frequency questionnaire combined with data of national monitoring programs on pesticide residues in food. Among those with non-null daily intake in >10% women (n=105), we focused on substances (n=60) with suspected endocrine disrupting properties or susceptible to impair the development of male reproductive organs. We used logistic regression to assess the risk of hypospadias in association with the dietary daily intake of 1) pesticides grouped by chemical family, or 2) individual pesticides selected a priori as the best predictors using cross-validated Elastic-Net model. Results: An increased risk of hypospadias was found statistically significant for the group of anilinopyrimidine pesticides (3rd vs 1 st and 2nd tertiles of exposure; OR=2.26, 95% CI: 1.25 to 4.11), for the organochlorine pesticides family (3rd vs 1 st and 2nd tertiles; OR=2.16, 1.20; 3.91) and for the group of amide pesticides (3rd vs 1 st and 2nd tertiles; OR=1.95, 1.08; 3.52). Three individual pesticides (among 60) were selected by the Elastic-Net procedure and showed increased risk of hypospadias for λ-cyhalothrin (3rd vs 1 st and 2nd tertiles, OR=2.34, 1.26; 4.42) and for cyprodinil (3rd vs 1 st and 2nd tertiles; OR=1.66, 0.90; 3.10) and DDT (3rd vs 1 st and 2nd tertiles; OR=1.72, 0.95; 3.15). Conclusion: Although the number of cases is small, our results are consistent with existing literature that have suggested increased risk of hypospadias in association with organochlorine pesticides. A confirmation with biomonitoring data would be give strength to the results.